DesR349P Mutation Results in Ultrastructural Disruptions and Compromise of Skeletal Muscle Biomechanics Already at Preclinical Stages in Young Mice before the Onset of Protein Aggregation - Diermeier, Stefanie; Haug, Michael; Reischl, Barbara; Buttgereit, Andreas; Schürmann, Sebastian; Spörrer, Marina; Goldmann, Wolfgang; Fabry, Ben; Elhimine, F.; Stehle, Robert; Pfitzer, Gabriele; Winter, L.; et al. (Elsevier (Cell Press) / Biophysical Society, 2016)
Mutations in the extra-sarcomeric protein desmin give rise to protein aggregate myopathies that interfere with cellular function. The R350P mutation is the most common human desminopathy. A murine DesR349P model of human DesR350P desminopathy was previously engineered. In this study, we followed the hypothesis of whether muscle cytoarchitecture and biomechanical properties are already altered in preclinical stages of R349P desminopathy. We applied non-linear second harmonic generation (SHG) and 2-photon fluorescence morphometry analysis to single fibres of fast- and slow-twitch muscle to analyze sarcomeric architecture and nuclear morphology. We found a vast disruption of the lateral sarcomere lattice (indicated by large ‘vernier’ densities) and myofibrillar angular deviations (indicated by cosine angle sums) in single DesR349P fibres. Homozygous fibres were more severely affected than heterozygous. The former showed a marked nuclear pathology with spheric nuclei, increased nuclear number and density. For biomechanics, we assessed active and passive properties. Axial stiffness of DesR349P muscle was much increased, both in fibre and myofibrillar homozygous bundles. Lateral stiffness of the membrane complex in myoblasts was increased in cells heterozygous for DesR349P while homozygous were similar to wt. Caffeine-induced force was compromised in heterozygous fibre bundles but increased in homozygous bundles. This was explained by a marked shift of myofibrillar Ca2+ sensitivity: heterozygous bundles being less sensitive but homozygous more sensitive to Ca2+. This points towards a specific compensatory mechanism in homozygous mutation to cope with otherwise compromised force production already at preclinical stages of desminopathy. Our findings provide a very first complete picture to explain compromised force in heterozygous DesR350P patients: increased muscle stiffness, higher susceptibility towards stretch-induced injury, disrupted myofibrillar alignment and compromised active force productio